Bright solid-state red-emissive BODIPYs: facile synthesis and their high-contrast mechanochromic properties. Issue 12 (11th February 2019) - Duan, Chong; Zhou, Yibin; Shan, Guo-Gang; Chen, Yuncong; Zhao, Weijun; Yuan, Dandan; Zeng, Lintao; Huang, Xiaobo; Niu, Guangle
Abstract : We first report several bright solid-state red-emissive BODIPYs with high fluorescence quantum yields for unusual high-contrast mechanohypsochromism. Abstract : Organic compounds with bright solid-state emission are emerging as versatile materials in many fields. However, traditional fluorescent dyes generally show high-emissive fluorescence in solution but faint or quenched emission in the solid state. Therefore, it remains a great challenge to develop bright solid-state emissive materials based on traditional fluorescent dyes. Herein, we report several solid-state emissive meso -substituted BODIPYs (PhMe3 -BODIPY, PhMe-BODIPY, Ph-BODIPY andMe-BODIPY ) obtained by using a simple two-step synthesis. Interestingly, these BODIPYs exhibit bright dual-state emission (DSE) with green fluorescence (512–520 nm, fluorescence quantum yield Φ F is up to 85%) in THF and solid-state red emission (601–632 nm, Φ F is up to 32.2%) in the crystalline state. The highly emissive fluorescence in the crystalline state is demonstrated to be due to the formation of J-aggregation. More importantly, the single crystals of the meso -aryl-substituted BODIPYs exhibit an unusual high-contrast mechanochromic property, which displays remarkable fluorescence color changes from red to yellow upon gentle grinding due to the transition from single crystals to microcrystals. Furthermore, strong grinding completely destroys the J-aggregation and leads to the transformation from microcrystals to a free state, hence the fluorescence color becomes green after strong grinding.